Efektivitas Pojk Stimulus Dampak Covid-19 Untuk Melindungi Umkm : Studi Di Kecamatan Entikong, Kabupaten Sanggau, Kalimantan Barat - Rohani, Siti; Yaniza, Tiza (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
This study aims to determine the role of economic law in assisting MSME actors during the COVID-19 pandemic in Entikong District, Sanggau Regency, West Kalimantan with the issuance of Financial Services Authority Regulation Number 11/POJK.03/2020. So that MSME actors in the Entikong District, Sanggau Regency, West Kalimantan, feel the benefits of Financial Services Authority Regulation Number 11/POJK.03/2020 in dealing with the Covid 19 pandemic and continuing people's economic activities. Based on research and data analysis, information was obtained that the role of economic law in assisting MSME actors during the COVID-19 pandemic in Entikong District, Sanggau Regency, West Kalimantan with the issuance of Financial Services Authority Regulation Number 11/POJK.03/2020 is a form of embodiment of the role of the State in protecting MSME business actors and community economic development by issuing regulations in the economic sector to help the community in this case including Micro, Small and Medium Enterprises affected by the impact of Covid 19 Regarding National Economic Stimulus as a Countercyclical Policy for the Impact of the 2019 Coronavirus Disease Spread. the Entikong Sub-district, Sanggau Regency, West Kalimantan has not yet benefited from the Financial Services Authority Regulation Number 11/POJK.03/2020 in dealing with the Covid 19 pandemic, due to the lack of information that is easily understood by MSMEs and banks to overcome the pandemonium mic Covid-19 in Entikong District, Sanggau Regency, West Kalimantan and the Financial Services Authority Regulation Number 11/POJK.03/2020. So that MSME business actors still allow them to run their business to get clarity from the bank on the regulation.